VALUASI EKONOMI JASA LINGKUNGAN OBYEK WISATA ALAM TRACKING MANGROVE BUNGKUTOKO KOTA KENDARI - La Baco S. (Jurnal Ecogreen, 2017)
Nature Tourism Area Tracking Mangrove Bungkutoko is one of nature tourism area that much favored by society of Kendari City. This is because this area has a fairly good mangrove ecosystem, located not far from downtown Kendari and easily accessible. The purpose of this study is to analyze the economic value of tourist areas Tracking Mangrove Bungkutoko. This research is a survey research conducted using the method of travel cost (travel cost method). The application of this method is done through interviews of selected respondents. Interviews of respondents were conducted using a pre-arranged questioner. The research variables include all components of travel expenses including transportation costs, accommodation, consumption, rent, entrance fee, parking and documentation. Travel expenses are the accumulation of these costs. The results showed that the average travel cost of respondents from Mandonga, West Kendari, Poasia, Baruga, Wua-wua, Kambu and Kadia sub districts amounted to 127.000 rupiah/person, 144.000 rupiah/person, 95.000 rupiah/person, 104.000 rupiah/person, 111.000 rupiah/person,105.000 rupiah/person and 95.000 rupiah/orang. The average value of travel costs of visitors attractions Tracking Mangrove Bungkutoko is 107.845 rupiah/person. Key Words: Economic Valuation, Tracking Mangrove, Travel Cost